Sistema web para controlar o balanceamento nutricional do gado leiteiro - Lucion, Vanessa (2020)
The biggest challenge in milk production is to provide the animal adequate and quality feed to obtain the maximum potential for milk production, while the costs of producing this feed do not interfere with the profitability of the property. However, frequently, the feed provided does not fit with the animal nutritional necessity, it can be left, not be enough or the nutrient in the feed provided is not adequate for the animal’s needs. Computational systems can be used to store milk production historical data, help the production process management and, between others, to be used to automatically define the quantity and the suitable or ideal types of feed for each animal, in its various productive phases. The web system makes access, storage and data search easier, facilitating analysis and decision making. The system proposed as a result of this work aims to assist in controlling the nutritional balance of the animals. Through the data collected since the birth, going through all stages of life, stipulating the adequate nutrition of each animal ́s life stage.